Operaciones de tecnología de la información y la eficiencia empresarial - Melchor Angeles, Miguel Angel (2023)
At the University of Lima, I learned a lot of technical and management knowledge that led me to successfully face my working life. I think that the clear difference is the way we manage projects and people, without neglecting the technical part. The knowledge acquired at the university allowed me to face these professional challenges, as well as the constant training in the changing world of technology. In the following pages I detail the different stages in my professional life that began as an intern in the operations area, later becoming systems operator, senior administrator, operations manager, production manager, project manager and finally as head of Customer Service. Technology. Thus, throughout my professional life I have faced different professional and personal challenges, which have shaped my professional character and have allowed me to develop and consolidate various skills, such as the management of complex projects, budget management, leadership of people and of multidisciplinary teams, IT operations, Operations in large-scale services. I learned over the years that the only constant is change and you have to adapt and learn to be able to lead, also that your family is as important as your work